Mirror movement-like muscle hypertonia stroke model based on ipsilateral weight load. Issue 3 (5th February 2020) - Matsuura, Akihiro; Karita, Tetsuya; Nakaso, Naoyuki; Kondo, Yoshihiro; Mori, Futoshi
Abstract : In stroke patients, muscle tone on the unaffected side is often increased during voluntary tasks. This is known as a mirror movement and might be an impediment to function recovery, but its neural background is still unclear. In this study, we investigated the effect of unilateral muscle hypertonia on ipsilateral cortical activity and contralateral motor function. Fourteen right-handed healthy young subjects lifted a weight of 10% body weight with the right upper limb to increase muscle tone (weight task), while no weight lifting was set as the control 'nonweight' task. We recorded the motor-evoked potential (MEP), resting motor threshold and H-reflex from the left flexor carpi radialis muscle during both tasks. To estimate the functional effect of the weight task, subjects performed the 'Purdue pegboard test', consisting of examination for 30 seconds (peg-30) and assembly for 60 seconds (peg assembly). Left-hand grip strength was also measured. When subjects performed the weight task, the MEP amplitude increased significantly and the MT decreased significantly. There was no significant difference of H-reflex amplitude between the two tasks. No significant difference of the peg-30 score was observed between weight and nonweight tasks, but the peg assembly score was significantly lower during the weight task. Grip strength showed a significant increase during the weight task. These results indicate that the present weight load model may have the potential to advance our understanding of the mechanisms underlying mirror movements after stroke.